Model System Supported Impedance Simulation of Composite Electrodes1. Issue 4 (17th July 2019) - Opitz, A. K.; Gerstl, M.; Bram, M.
Abstract: Current research on fuel electrodes of solid oxide cells (SOCs) is done either on model‐type pattern electrodes or by interpretation of impedance spectra measured on "real" porous paste electrodes. However, results obtained by both methods are not always straightforward to compare. To bridge this gap, in this study impedance spectra of 3D porous composite electrodes with a well‐defined geometry are simulated using elementary parameters from model‐type experiments. By independent variation of these elementary parameters, it is possible to analyze the influence of the individual elementary processes on the overall electrode performance without the issue of changing its microstructure, which usually occurs when changing materials in case of real porous electrodes. The obtained results identify the electrochemical reaction resistance as the parameter with the highest impact on the polarization resistance of porous electrodes. This study thus provides a basis for a knowledge‐based improvement of existing and novel composite fuel electrodes. In addition, the developed transmission line model is used for critically examining the common method of deconvolution of impedance data measured on real porous composite electrodes, which often relies on the assumption of elementary processes being represented by a serial connection of simple R||C elements.